Effect of Seedling Ages and Generations on The Morphology and Productivity of Tropical Alfalfa (Medicago sativa L. cv Kacang Ratu BW) - Kharunisa, Laras; Salsabila, Zidna Ilma; Juniardi, Ricky; Astuti, Andriyani; Suwignyo, Bambang (The Islamic Education and Multiculturalism Foundation, 2025)
The productivity of ruminant livestock is highly dependent on the availability of quality forage feed that meets their needs. Alfalfa is palatable and rich in nutrients, minerals and vitamins that livestock may require. This study aimed to investigate the effect of age of tropical alfalfa seedlings and generations on the morphology and productivity of tropical alfalfa (Medicago sativa L. cv Kacang Ratu BW). The research design is Completely Randomized Design using 2 × 2 with two factorial and three replications. Evaluation of the effect of seedling ages (1 month and 2 months) and generations (F2 and F3) on plant growth (height of plants, branches, and leaves of plants) and productivity were recorded. The differences between treatments were continued, analysis with Duncan’s Multiple Range Test is used. The result showed that seedling ages in 2 months produced the highest plant productivity (P<0,05). Among the generations tested, F3 emerged as the top plant productivity (P<0,05). Plants productivity consisted of height of plants, number of branches, number of leaves. The study concluded that planting alfalfa seedlings at two months old significantly influences plant height and leaf count, resulting in better overall growth. However, the influence of generation, specifically F3, affects plant height. The number of branches does not significantly affect either seedling age or generation.